2017
DOI: 10.1097/phm.0000000000000782
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Effect of Strength Training on Pain and Sleep in Patients With Fibromyalgia?

Abstract: Strength training is safe and effective in treating people with fibromyalgia, and a significant decrease in sleep disturbances occurs after 8 wks of intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 23 publications
3
53
1
Order By: Relevance
“…Our results did not show significant differences in sleep quality after 4 weeks of intervention. However, other studies such as those by Andrade et al and Bircan et al showed that RT had a significant benefit for sleep disturbances. Bircan et al compared the effects of RT and aerobic exercise and reported that both interventions resulted in significant improvement in sleep quality; meanwhile, no significant difference was found between the groups.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Our results did not show significant differences in sleep quality after 4 weeks of intervention. However, other studies such as those by Andrade et al and Bircan et al showed that RT had a significant benefit for sleep disturbances. Bircan et al compared the effects of RT and aerobic exercise and reported that both interventions resulted in significant improvement in sleep quality; meanwhile, no significant difference was found between the groups.…”
Section: Discussionmentioning
confidence: 88%
“…Because pain is the predominant symptom in FM, with a large impact on quality of life, several authors have examined this variable. Bircan et al, Gavi et al, Kingsley et al, and Andrade et al evaluated the effect of RT on pain and they reported divergent results. Andrade et al evaluated patients with FM after 8 weeks of RT three times a week; at the end of the study, no significant difference in pain was observed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations